Replacement names for two preoccupied generic names in Arthropoda - Tonini, Lorena; Silva, Juliana Paulo Da; Filho, Arlindo Serpa; Freitas, Joelcio (Zootaxa, 2016)
The genus Ransonia Blandin, 1979 (Arachnida: Araneae) was established with description of a new species, Ransonia mahasoana of the family Pisauridae (Arachnida: Araneae) endemic from Mahasoa, Madagascar. Unfortunately, this name is preoccupied by Ransonia Kramp, 1947, a genus of the family Rhopalonematidae (Hydrozoa: Trachymedusae) with only one species, Ransonia (Aglantha) krampi Ranson (1932), from Gibraltar, Mediterranean. According to article 60 of the International Code of Zoological Nomenclature a new substitute name is necessary, since Ransonia Blandin, 1979 does not have a junior synonym applicable and is a junior homonym of another genus. Therefore, we propose a replacement name for the spider genus as follows.